Differences in throughfall drop size distributions in the presence and absence of foliage. Issue 3 (17th February 2016) - Nanko, Kazuki; Hudson, Sean A.; Levia, Delphis F.
ABSTRACT: Throughfall drop size distributions (DSDs) are important for plant–soil interactions. This is the first known study to quantify differences in throughfall DSDs with the presence and absence of foliage. Employing a disdrometer, three parameters solely representing throughfall drip were measured and calculated: maximum drop diameter (DMAX ), median volume diameter of drops (D50 DR ) and relative volume percentage of drops ( p DR ). Beneath Liriodendron tulipifera L. in Maryland (USA), DMAX, D50 DR and p DR were substantially larger when the canopy was unfoliated. In fact, the presence or absence of foliage was one of the primary factors affecting all three throughfall DSDs along with air temperature, according to the boosted regression tree analysis. Experimental results were attributed to differing physical properties of intercepted water between foliated and unfoliated periods and differential water behavior on leaves and bark. Future work should examine the effects of concentrated drip points on the development of throughfall-induced hot spots.Editor M.C. Acreman;Associate editor F. Hattermann